Death in custody: how America ignores the truth and what we can do about it - Mitchell, Roger A. (Health equity in America, 2023)
"This work focuses on the stories of several individuals who died while in custody to illustrate the long history of policy and practice that at best provides toothless regulation (often unfunded, or without accountable parties), and at worst is officially dismissive of the human lives lost, deliberately making it harder to get to the truth. The authors also tell the stories of activists and journalists, who have often been the ones making the greatest effort to uncover the true scope of deaths in custody"--